THE EFFECTIVENESS OF 16 WEEKS PHYSICAL EXERCISE ON BODY COMPOSITION, STRESS LEVEL, AND FITNESS STATUS IN COLLEGE STUDENTS - Nabillah, Azry Ayu; Safei, Imam; Tarigan, Boy Sembaba; Lestari, Erny Amalia; Ramadhani, Africo (MEDIKORA, 2024)
The density of academic schedules, academic tasks, lifestyle changes, and social pressures often color students' experiences, which can make them vulnerable to various health problems. One of the main issues faced by students is unhealthy changes in body composition, high stress levels, and the risk of cardiovascular disease. The aim of this study is to investigate the effectiveness of physical exercise on body composition, stress levels, and cardiovascular health in students. This research method employs an experimental approach with a pretest-posttest without control group design. The total subjects in this study were 600 students (300 males and 300 females), with an average age of 18.92 ± 4.79 years, weight of 56.05 ± 12.08 kg, and height of 163.91 ± 8.24 cm. The results of this study provide evidence that physical exercise performed for 16 weeks can help improve fitness status, maintain ideal body composition, and have an impact on reducing stress levels in students. Thus, this physical exercise program can be recommended for all students and educators, especially in the field of sports, to maintain students' fitness and mental health in the college environment.Padatnya jadwal perkuliahan, tugas akademik, perubahan gaya hidup, dan tekanan sosial seringkali mewarnai pengalaman mahasiswa, hal ini dapat menyebabkan mereka rentan terhadap berbagai masalah kesehatan. Salah satu masalah utama yang dihadapi oleh mahasiswa adalah perubahan komposisi tubuh yang tidak sehat, tingkat stres yang tinggi, dan risiko penyakit kardiovaskular. Tujuan penelitian ini adalah untuk menginvestigasi efektivitas latihan fisik terhadap komposisi tubuh, tingkat stres, dan kardiovaskular pada mahasiswa. Metode Penelitian ini menggunakan metode eksperimental dengan pendekatan pretest-posttest without control group design. Total subjek dalam penelitian ini berjumlah 600 mahasiswa (300 laki-laki dan 300 perempuan). rata-rata usia 18.92 ± 4.79 tahun, berat badan 56.05 ± 12.08  kg, dan tinggi badan 163.91 ± 8.24 cm. Hasil penelitian ini memberikan bukti bahwa latihan fisik yang dilakukan selama 16 minggu dapat membantu meningkatkan status kebugaran  (VO2Max, p=0.001), menjaga komposisi tubuh agar tetap ideal (berat badan, p=0.512) serta berpengaruh terhadap penurunan tingkat stress pada mahasiswa (PSS, p=0.001). Dengan demikian program latihan fisik ini dapat dijadikan sebagai rekomendasi bagi semua mahasiswa maupun tenaga pengajar khususnya di bidang olahraga dalam menjaga kebugaran dan kesehatan mental mahasiswa dilingkungan perguruan tinggi